Serum cytokine levels in patients with chronic low back pain due to herniated disc: analytical cross-sectional study - Kraychete, Durval Campos; Sakata, Rioko Kimiko; Issy, Adriana Machado; Bacellar, Olívia; Santos-Jesus, Rogério; Carvalho, Edgar Marcelino (São Paulo Medical Journal, 2010)
CONTEXT AND OBJECTIVE: The role of immune response and proinflammatory cytokines in the pathogenesis of chronic pain has been of growing interest. In order to evaluate whether there is any association between disc herniation and elevated cytokine levels, we measured cytokine levels in patients with chronic low back pain and in healthy subjects. DESIGN AND SETTING: Analytical cross-sectional study at the Pain Clinic of Universidade Federal da Bahia (UFBA). METHODS: Cytokine levels were measured using the enzyme-linked immunosorbent assay (ELISA) technique on 23 patients with low back pain (G1) and on 10 healthy subjects (G2). RESULTS: The levels of tumor necrosis factor-alpha [TNF-alpha] (G1 = 5.6 ± 2.3 pg/ml; G2 = 1.6 ± 0.5 pg/ml; P = 0.01) and interleukin-6 [IL-6] (G1 = 4.1 ± 3.0 pg/ml; G2 = 0.9 ± 0.4 pg/ml; P = 0.01) were higher in G1. There were no statistically significant differences in relation to interleukin-1 [IL-1] (G1 = 0.5 ± 0.3 pg/ml; G2 = 0.5 ± 0.1 pg/ml; P = 1) or soluble tumor necrosis factor receptor [sTNF-R] (G1 = 572 pg/ml ± 36; G2 = 581 ± 50 pg/ml; P = 0.87). CONCLUSION: The patients with chronic low back pain due to disc herniation presented higher levels of TNF-alpha and IL-6, but not of IL-1 or sTNF-R.